2012
DOI: 10.5005/jp-journals-10029-1003
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study on Dental Air Force Home Dental Cleaning System on Adult Chronic Periodontitis Patients and its Assessment to C-Reactive Protein Levels

Abstract: Aim:The study was outlined to determine and assess the C-reactive protein (CRP) level in chronic periodontitis patients and to assess the CRP values after using Dental Air Force home dental cleaning system. Materials and methods:A total of 100 adult chronic periodontitis subjects were recruited voluntarily for this study. Clinical assessment of plaque index, gingival index, probing depth, clinical attachment level and C-reactive protein (CRP) levels were made prior to phase-1 therapy and at 7th and 15th day po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A reduction also occurred in nondiabetics as well [5]. As a review, the British Medical Journal (BMJ) reported a 1% reduction in HbA1c levels gives the following reduction in combined diabetes-related endpoints [6]: Dental Air Force is a non-invasive home management tool that has shown a reduction of Pg, Aa, Fn, and Pi by 500% over the course of the study, unlike periodontal therapy followed by toothbrush maintenance [7]. It is an FDA approved for marketing medical device that mitigates the pathogens of periodontal disease that initiates a patient's chronic inflammatory host response Figure 2.…”
Section: Opinionmentioning
confidence: 84%
See 1 more Smart Citation
“…A reduction also occurred in nondiabetics as well [5]. As a review, the British Medical Journal (BMJ) reported a 1% reduction in HbA1c levels gives the following reduction in combined diabetes-related endpoints [6]: Dental Air Force is a non-invasive home management tool that has shown a reduction of Pg, Aa, Fn, and Pi by 500% over the course of the study, unlike periodontal therapy followed by toothbrush maintenance [7]. It is an FDA approved for marketing medical device that mitigates the pathogens of periodontal disease that initiates a patient's chronic inflammatory host response Figure 2.…”
Section: Opinionmentioning
confidence: 84%
“…In one published six month study using Dental Air Force as an adjunct to periodontal therapy, a 1.04% reduction in HbA1c was observed in a population of 50 patients in Figure 1. A reduction also occurred in nondiabetics as well [5]. As a review, the British Medical Journal (BMJ) reported a 1% reduction in HbA1c levels gives the following reduction in combined diabetes-related endpoints [6]: Dental Air Force is a non-invasive home management tool that has shown a reduction of Pg, Aa, Fn, and Pi by 500% over the course of the study, unlike periodontal therapy followed by toothbrush maintenance [7].…”
Section: Opinionmentioning
confidence: 99%
“…The water flushes away the bacteria and debris offs the surfaces of the teeth. 8 Dental Air Force home dental cleaning system with access to subgingival area lead to removal of biofilm and prevent further proliferation of periodontopathic microorganisms.…”
Section: Graphmentioning
confidence: 99%